African swine fever virus MGF505–6R attenuates type I interferon production by targeting STING for degradation - Yao, Manman; Cao, Hua; Li, Wentao; Hu, Zihui; Rong, Zhenxiang; Yin, Mengge; Tian, Linxing; Hu, Dayue; Li, Xiangmin; Qian, Ping (Frontiers in Immunology, 2024)
African swine fever (ASF) is an acute hemorrhagic and devastating infectious disease affecting domestic pigs and wild boars. It is caused by the African swine fever virus (ASFV), which is characterized by genetic diversity and sophisticated immune evasion strategies. To facilitate infection, ASFV encodes multiple proteins to antagonize host innate immune responses, thereby contributing to viral virulence and pathogenicity. The molecular mechanisms employed by ASFV-encoded proteins to modulate host antiviral responses have not been comprehensively elucidated. In this study, it was observed that the ASFV MGF505-6R protein, a member of the multigene family 505 (MGF505), effectively suppressed the activation of the interferonbeta (IFN-β) promoter, leading to reduced mRNA levels of antiviral genes. Additional evidence has revealed that MGF505-6R antagonizes the cGAS-STING signaling pathway by interacting with the stimulator of interferon genes (STING) for degradation in the autophagy-lysosomal pathway. The domain mapping revealed that the N-terminal region (1-260aa) of MGF505-6R is the primary domain responsible for interacting with STING, while the CTT domain of STING is crucial for its interaction with MGF505-6R. Furthermore, MGF505-6R also inhibits the activation of STING by reducing the K63-linked polyubiquitination of STING, leading to the disruption of STING oligomerization and TANK binding kinase 1 (TBK1) recruitment, thereby impairing the phosphorylation and nuclear translocation of interferon regulatory factor 3 (IRF3). Collectively, our study elucidates a novel strategy developed by ASFV MGF505-6R to counteract host innate immune responses. This discovery may offer valuable insights for further exploration of ASFV immune evasion mechanisms and antiviral strategies.